Symbolic cosmopolitanism, structural hedonism: organic hummus and cultural globalization in Israel - Grosglik, Rafi (Hagar: Studies in Society and Culture, 2012)
Hummus, one of the most common foods in Israel, was appropriated several decades ago as an icon of Israeli culture and nationality. Organic hummus-a recent version of the dish-appeared due to global-cultural trends of ethical and reflexive food consumption. It is customary to see organic food as representing locality, health, ecology and social justice. But it also embodies representations of globalism and westernism, mainly because of its integration in the global industrial system and its origin among the post-materialistic social elite in Western countries. This article deals with the encounter of the global and local as embodied in organic hummus in Israel. This look at the production, distribution and consumption of organic hummus uncovers social and political layers embedded in the dish and sheds light on several paradoxical aspects. I argue that the global socioeconomic conditions and ideas embedded in the concept of organic attached to hummus allow the imagined relocalization of the dish. Hummus is a dish perceived as representing rootedness, carthiness and local simplicity, but nowadays, in its organic version, it wears an localization of the dish. Hummus is a dish perceived as representing rootedness, carthiness and local simplicity, but nowadays, in its organic version, it wears an economic and symbolic framework of global values used by the Israeli westernizing elite to demonstrate a symbolic cosmopolitan identity.